Evaluating the implementation of person-centred care and simulation-based learning in a midwifery education programme in the Democratic Republic of Congo: a study protocol - Frida Temple; Ewa Carlsson Lalloo; Marie Berg; Urban Berg; Alumeti Munyali Désiré; Olivier Nyakio; Aline Mulunda; Malin Bogren (Global Health Action)
Background Investing in midwives educated according to international standards is crucial for achieving Sustainable Development Goals in maternal and newborn health. Applying a person-centred care approach and using simulation-based learning to improve the learning experience for midwifery students may enhance the quality of childbirth care. This protocol describes a study evaluating the implementation of person-centred approach and simulation-based learning in childbirth as part of a midwifery education programme at the Evangelical University in Africa, DRC. Methods The research will be exploratory and guided by an implementation research framework. Ethical approval has been obtained. Facilitators working at the programme’s five clinical practice sites will be trained in: 1) Introducing person-centred childbirth care using a training programme called‘Mutual Meetings’; and 2) integrating simulation-based learning, specifically by using the three courses: Essential Care of Labor, Bleeding after Birth, and Vacuum Extraction. Data will include interviews with midwifery students, facilitators and clinical preceptors, and maternal and neonatal outcomes from birth registers. Discussion By integrating a validated and culturally adapted person-centred care training programme and simulation-based learning into a midwifery education programme and clinical practice sites, the findings from the study anticipate an improvement in the quality of childbirth care. Training facilitators in these methodologies aim to effectively mitigate maternal and neonatal adverse outcomes. The findings are expected to provide valuable recommendations for governments, policymakers, and healthcare providers in the DRC and beyond, contributing to significant improvements in midwifery education and aligning with global health priorities, including the Sustainable Development Goals. Trial registration The study was registered retrospectively with the ISRCTN registry on the 23rd of February 2024. The registration number is: ISRCTN10049855.